2017
DOI: 10.1177/1066896917734371
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of Chronic Lymphocytic Leukemia/Small Lymphocytic Lymphoma in a Warthin Tumor: Case Report and Literature Review

Abstract: Warthin tumor is the second most common salivary gland neoplasm. It occurs more commonly in males than in females. Malignant transformation in Warthin tumor is a rare but well-recognized phenomenon; however, the development or presentation of lymphoma in a Warthin tumor is rare. An 80-year-old man presented with painless mass of the right parotid gland of 2 years duration with recent ulceration of the overlying skin and right cervical lymphadenopathy underwent a surgical resection of parotid mass and biopsy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Molecular detection, FISH analysis, gene rearrangement and flow cytometry (FCM) analysis were not performed in most of these cases. Only a few cases were reported for FCM detection[19], immunoglobulin monoclonal gene rearrangement[1,21], PCR detection[23] or detection of bcl-2 mcr/JH fusion DNA sequences[1]. Our case was detected by the FISH method, and the result showed that only bcl-6 break-apart rearrangement (3q27) was observed in tumor cells of DLBCL.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Molecular detection, FISH analysis, gene rearrangement and flow cytometry (FCM) analysis were not performed in most of these cases. Only a few cases were reported for FCM detection[19], immunoglobulin monoclonal gene rearrangement[1,21], PCR detection[23] or detection of bcl-2 mcr/JH fusion DNA sequences[1]. Our case was detected by the FISH method, and the result showed that only bcl-6 break-apart rearrangement (3q27) was observed in tumor cells of DLBCL.…”
Section: Discussionmentioning
confidence: 82%
“…We concluded that the most common subtypes of lymphoma were FLs (10 cases)[1-10], followed by Hodgkin’s lymphoma (4 cases)[11-14] and diffuse large B cell lymphoma (6 cases)[4,15-18]. The others were small lymphocytic lymphoma/chronic lymphocytic leukemia (3 cases)[19-21], mantle cell lymphoma (1 case)[22], extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue (1 case)[23], Lennert lymphoma (1 case)[24], peripheral T-cell lymphoma (2 cases)[25,26], and T lymphoblastic leukemia/lymphoma (1 case)[27]. In these patients, 4 cases of T-cell lymphoma and 25 cases of B-cell lymphoma were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple tumours may be considered from three perspectives: according to their histological type with identical or different histology, time of development as synchronous or metachronous and localisation as unilateral, bilateral and multiple . The rare occurrence of other primary malignant salivary gland tumours could also be a result of malignant transformation of the epithelial or lymphoid component of WT …”
Section: Association With Other Salivary Gland Tumours and Other Extrmentioning
confidence: 99%
“…Recurrence of WT is probably associated with the multifocality of WT or inadequate excision . In rare cases—about 1%‐ malignant transformation of WT may occur, ie, squamous cell carcinoma or other carcinoma may develop from the epithelial component, and lymphoma may involve the lymphoid component . Some patients with malignant transformation of WT give a history of radiation.…”
Section: Prognosis Of Wtmentioning
confidence: 99%
See 1 more Smart Citation